S100B as a surrogate marker for successful clot lysis in hyperacute middle cerebral artery occlusion. Issue 3 (1st March 2003) - Foerch, C; Du Mesnil de Rochemont, R; Singer, O; Neumann-Haefelin, T; Buchkremer, M; Zanella, F E; Steinmetz, H; Sitzer, M
Abstract : Objectives: The astroglial protein S100B is a marker of cerebral tissue damage. This study investigated whether the serum kinetic of S100B may serve as a surrogate marker of successful clot lysis and early recanalisation (<6 hours) in hyperacute proximal middle cerebral artery (MCA/M1) occlusion. Methods: The authors prospectively included 23 patients (mean (SD) age, 70.2 (11.0) years) presenting with MCA/M1 occlusion on magnetic resonance angiography (n=18), intra-arterial angiography (IA; n=2), or transcranial Doppler sonography (TCD; n=3) within five hours after symptom onset. Rates of recanalisation and their point of time were determined using TCD or IA. Individual S100B values were determined at hospital admission, every eight hours within the first three days, and at 12 hour intervals from day 4 to day 6. Additionally, the S100B area under the curve (AUC) and the S100B peak value were obtained. Results: Early recanalisation (<6 hours after symptom onset, n=7) was associated with a significantly lower mean S100B AUC compared with no recanalisation (22.2 (40.1) versus 406.8 (284.4) μg/l per hour; p<0.001). Using receiver operating calculations, a single S100B value obtained 48–96 hours after stroke onset of less than 0.4 μg/l (cut off point) provided a 86% sensitivity and 100% specificty for sufficient MCA/M1 clot lysis <6 hours. The overall accuracy for a single S100B value obtained in the 48–96 hours time window was as high as for the AUC (95.7%). Conclusion: A single S100B value <0.4 μg/l obtained 48–96 hours after stroke onset indicates succesful clot lysis <6 hours in MCA/M1 occlusion with a high degree of accuracy. Thus, determination of a single S100B value may serve as a surrogate marker of early and sufficient MCA/M1 recanalisation in large scale thrombolytic studies.